NETIZENS' PERCEPTION OF MUSEUM PUSAKA NIAS AS A TOURISM DESTINATION ON THE FACEBOOK PLATFORM IN GUNUNGSITOLI - Zai, Asnini Junita; Waruwu, Elvi Krisnawati; Hulu, Delan Septiani; Harefa, Afore Tahir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study examines netizens' perceptions of the Nias Heritage Museum as a tourism destination through analysis of comments on the museum's Facebook platform. Using a qualitative descriptive approach, the research analyzes Facebook posts and comments from 2023-2024 to understand how social media users perceive and engage with the museum online. The study employs sociolinguistic analysis to examine language variation, identity expression, cultural context, and language functions in user comments. Findings indicate generally positive perceptions of the museum, with netizens using both Indonesian and the Nias regional language to express cultural pride and identity. The research reveals that posts with diverse language use and strong cultural context generate higher engagement. Additionally, the study demonstrates the effectiveness of Facebook as a promotional tool for the museum, highlighting the platform's ability to reach a wide audience and foster community interaction. This research contributes to understanding digital communication strategies for cultural heritage sites and offers insights for optimizing social media engagement in cultural tourism contexts.